Youth and surveillance in the Facebook era: Policy interventions and social implications. Issue 9 (October 2015) - Montgomery, Kathryn C.
Abstract: Facebook's meteoric rise—from a small Harvard-based website that began in 2004, to a global digital platform with a membership of 1.2 billion people a decade later—has made it one of the most profitable and high-profile corporations in today's contemporary digital culture. Its aggressive marketing and data collection practices, however, have placed Facebook at the center of public policy debates over consumer privacy in the Big Data era. This paper explores those controversial practices, focusing especially on their effects on youth. More than 80% of teens use social media, which have become an essential arena for personal and social development, and which may well be altering some of young peoples' behavior patterns. But except for a handful of studies (mostly published in marketing journals) the growing body of academic literature on social media and youth has ignored the role of marketplace forces. Yet economic imperatives and powerful e-commerce business models are fueling the growth of these new platforms, shaping their structures and operations, and both responding to and influencing user behaviors. The driving force behind the growth of social media—and, indeed, all digital media—is a complex set of data collection, tracking, and targeting systems that monitor and monetize individual users' behaviors as well as their interactions with friends and acquaintances. Facebook's marketing, data collection, tracking, and targeting operations are specially attuned to key aspects of adolescent development, both tapping into young peoples' needs and taking advantage of their unique vulnerabilities. Because of adolescents' emotional volatility and their tendency to act impulsively, they are more vulnerable than adults to such techniques as real-time bidding, location targeting (especially when the user is near a point of purchase), and "dynamic creative" ads tailored to their individual profile and behavioral patterns. Given the unique role that digital media play in the lives of young people, new strategies will be required to ensure that their privacy is enshrined as a fundamental right. One way to accomplish this is to develop a set of "Fair Information and Marketing Principles for Children and Teens, " drawn from the long-established and well-recognized Fair Information Privacy Practices. These principles should take into account the unique needs and vulnerabilities of youth, and be designed to balance the ability of young people to participate fully in the contemporary media culture—as producers, consumers, and citizens—with the governmental and industry obligation to ensure they are not subjected to unfair, manipulative, and deceptive data collection and marketing practices. In order to achieve these goals, advocacy organizations, educators, parents, scholars, and youth need to work together as part of a broad, social movement, making privacy for children and youth part of the larger policy agenda on behalf of all consumers and citizens.